1984
DOI: 10.1056/nejm198410183111602
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Arrest during Rem Sleep in Young Adults

Abstract: Four apparently healthy young adults with vague chest symptoms during the day, two of whom had infrequent syncope while ambulatory at night, had periods of asystole up to nine seconds in duration occurring repeatedly during rapid-eye-movement (REM) sleep. Extensive evaluations, including electrophysiologic studies in two patients, were normal. It is therefore suggested that the underlying pathophysiology involved autonomic dysfunction. REM sleep-related sinus arrests such as these, which may occur in apparentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
13

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(78 citation statements)
references
References 11 publications
2
63
0
13
Order By: Relevance
“…Note, however, that bradyarrhythmias have been reported in REM sleep even in healthy young subjects. 249 If the underlying cardiac conduction system is normal and there is no significant thyroid dysfunction, bradyarrhythmias or heart block, both of which occur during apneic periods, may be treated effectively with CPAP or, if necessary, with tracheostomy. 230,244,245,250 Observational data suggest that the presence of untreated OSA in patients after successful cardioversion for atrial fibrillation is associated with an 82% risk for recurrence of atrial fibrillation within 1 year, about double the risk seen in effectively treated OSA patients after cardioversion.…”
Section: Treatment Of Sleep Apnea: Effects On Arrhythmiasmentioning
confidence: 99%
“…Note, however, that bradyarrhythmias have been reported in REM sleep even in healthy young subjects. 249 If the underlying cardiac conduction system is normal and there is no significant thyroid dysfunction, bradyarrhythmias or heart block, both of which occur during apneic periods, may be treated effectively with CPAP or, if necessary, with tracheostomy. 230,244,245,250 Observational data suggest that the presence of untreated OSA in patients after successful cardioversion for atrial fibrillation is associated with an 82% risk for recurrence of atrial fibrillation within 1 year, about double the risk seen in effectively treated OSA patients after cardioversion.…”
Section: Treatment Of Sleep Apnea: Effects On Arrhythmiasmentioning
confidence: 99%
“…GUILLEMINAULT et al [12] reported asystolic periods up to 9 s in duration only during REM sleep in four apparently healthy young adults without sleep-related breathing disorder. NEVINS [13] describ-ed the case of a patient with heart failure who developed episodes of AV block also during REM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Most arrhythmias that occur during sleep are detected incidentally on Holter monitoring and are benign, however, 15% of fatal ventricular arrhythmias still occur in sleep resulting in sudden nocturnal death. 1 Bradyarrhythmia, sinus pauses > 2 seconds and atrioventricular (AV) conduction delays commonly occur during sleep in young and healthy individuals specially more frequently in young athletes and less frequently in those over 80 years of age. In a series, long sinus pauses upto 9 seconds, were reported in 4 healthy athletes without cardiac disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Human beings spend approximately one-third of their lives asleep 1 . Although generally considered to be a peaceful stable period for the body and mind to rest and heal, sleep in fact represents a complex dynamic process involving dynamic changes in physiological state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation